Public Education on Stunting Prevention as an Effort to Produce Healthy Generation in Singkawang - Rochmawati, Ida; Yuniarsih, Rulida; Arisdiyoto, Iving; Amalia, Annisa Dina (LPPM Universitas Islam Sultan Agung, 2024)
Health problems related to nutritional status in children are still a global challenge, especially in developing countries, including Indonesia. Stunting is a condition where children under five experience malnutrition, which can be fatal to children's health, especially in the early days of life. West Kalimantan is one of the 12 provinces with the highest stunting cases in Indonesia in 2022, with the stunting prevalence rate at 27.8 percent. An educational activity was carried out to improve knowledge and understanding as well as community participation in stunting prevention and early detection programs in toddlers which are expected to directly motivate the community to participate in paying attention to the growth and development of their children so that their growth and development can be optimal. The target of this educational activity is parents of pre-school aged children. This service activity goes through three stages, namely the preparation stage, the implementation stage and the evaluation stage. In the preparation stage, the issue of public awareness of stunting was raised as a theme, targeting parents in Singkawang City. At the implementation stage, the service team collaborates with the Anugrah Clinic to provide socialization regarding stunting prevention to participants. At the evaluation stage, a post test was carried out to find out the extent to which the activity left impact. As a result of this service activity, it can be concluded that stunting is still an important issue or problem experienced by the people of West Kalimantan, including Singkawang. This is shown by the high prevalence of stunting and the low awareness and knowledge of the community, especially parents, about the dangers, causes and ways to prevent stunting early.